A deep genealogy of Japanese green nationalism from the long 19th century to the present - Hudson, Mark; Uchiyama, Junzo; Lindström, Kati; Šukelj, Katarina (Frontiers in Human Dynamics, 2025)
Employing the term “green nationalism” in the broad sense of nationalist ideologies that concern themselves with the natural environment, we trace a genealogy of green nationalist thought in Japan back to the start of the long 19th century. The changing contours of this discourse are mapped through five representative writers: Moto'ori Norinaga (1730–1801), Shigetaka Shiga (1863–1927). Testurō Watsuji (1889–1960), Takeshi Umehara (1925–2019) and Yoshinori Yasuda (b. 1946). Despite significant transformations in how Nature has been understood over the previous two and a half centuries, we identify five common trends in the discourse: (1) Japan as a “natural community;” (2) Japan as a harmonious nation where conflict comes from the outside; (3) a nativist concern with Japanese cultural and racial exceptionalism in opposition to China and the West; (4) a concern with protecting the natural resources of the nation for the exclusive benefit of the Japanese people; and (5) the view that an “authentic” Ur-identity can be found in archaic or traditional Japan. These ideas have been influential in Japanese society; however, their impact in fostering pro-environmentalist behaviour requires further analysis. Some of the complexities involved are illustrated by a brief examination of the role of green nationalism on school textbooks. We conclude that the radical, utopian elements of Japanese green nationalism have often been at odds with national educational policy. While the discursive constructs of Japanese green nationalism have been mobilised in some state policies, their capacity to encourage environmental action remains questionable.